2015
DOI: 10.1039/c5cp00424a
|View full text |Cite
|
Sign up to set email alerts
|

Chelerythrine–lysozyme interaction: spectroscopic studies, thermodynamics and molecular modeling exploration

Abstract: The binding of the iminium and alkanolamine forms of chelerythrine to lysozyme (Lyz) was investigated by spectroscopy and docking studies. The thermodynamics of the binding was studied by calorimetry. Spectroscopic evidence suggested that Trp-62 and Trp-63 in the β-domain of the protein are closer to the binding site; moreover, the binding site was at a distance of 2.27 and 2.00 nm from the iminium and alkanolamine forms, respectively, according to the Forster theory of non-radiation energy transfer. The equil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
53
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 78 publications
3
53
0
Order By: Relevance
“…(B) that the CD signal of lysozyme showed a considerable perturbation upon the addition of TBO. This clearly points toward the possibility of slight alterations in the tertiary structure and/or enhanced flexibility of lysozyme . Moreover, the observed spectral alterations in both near‐ and far‐UV CD regions make it clear that the binding of TBO with lysozyme results in the structural changes in lysozyme conformation.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…(B) that the CD signal of lysozyme showed a considerable perturbation upon the addition of TBO. This clearly points toward the possibility of slight alterations in the tertiary structure and/or enhanced flexibility of lysozyme . Moreover, the observed spectral alterations in both near‐ and far‐UV CD regions make it clear that the binding of TBO with lysozyme results in the structural changes in lysozyme conformation.…”
Section: Resultsmentioning
confidence: 84%
“…It is evident from Fig. (B) that major force of interaction involved in the binding of lysozyme with TBO is hydrophobic and hydrogen bond interaction . The calculated Gibbs energy change (Δ G ) value using the docking results for lysozyme–TBO system is −22.13 kJ mol −1 .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Recently our group has reported the interactions of 7‐hydroxyflavone, 3‐hydroxyflavone, naringenin and naringin with HEWL ,. In recent times, the interaction studies of several small ligands with HEWL have been reported . The multifarious pharmaceutical applications of dietary polyphenols due to their high bioactivity and low toxicity have accumulated tremendous interest among different research groups throughout the world.…”
Section: Introductionmentioning
confidence: 99%
“…[5,6] In recent times, the interaction studies of several small ligands with HEWL have been reported. [7][8][9][10] The multifarious pharmaceutical applications of dietary polyphenols due to their high bioactivity and low toxicity have accumulated tremendous interest among different research groups throughout the world. Flavonoids, a class of natural bioactive polyphenolic compounds found in various plants and fruits, are well recognized for their broad range of pharmaceutical and biological properties such as anti-oxidative, [11] anti-inflammatory, [12] anti-cancer, [13] anti-tumor, [14] etc and are also known to reduce the risk of diseases like cancer and stroke.…”
Section: Introductionmentioning
confidence: 99%